Perancangan Bak Penampungan untuk Pembuangan Limbah Coolant dari Mesin Broaching Menggunakan Software Solidwork dan ANSYS Simulasi - Lestyanto Ardi, Affan; Sena, Boni; Gusniar, Iwan Nugraha; Ujiburrahman; Oleh; Amanah, Nadia (Universitas Sarjanawiyata Tamansiswa, 2024)
Industrial waste is one of the most serious problems in the industrial world. Industrial wastewater treatment plants as one of the solutions to overcome these problems require holding tanks as the main part of the system. Holding tanks function as waste reservoirs before further processing. Thus, holding tanks play an important role in reducing the negative impact of waste on the environment and preventing damage to industrial facilities. The holding tank is designed using solidwork and ANSYS in order to ensure the reability and capability in relocatting the coolant waste water. From the results of the research on the design of wastewater reservoirs, the maximum total deformation subjected to a load of 0.00017735 MM is obtained, while the smallest total deformation value is 1.9705 MM. The results of the maximum stress or voltage subjected to a load of 0.17112 Mpa while the smallest stress value is 0.080072 Mpa. And for the results of the maximum strain or strain subjected to a load of 6.868 Mpa while for the smallest strain value is 7.7904 Mpa.